EFFECT OF ORAL AZITHROMYCIN AND METRONIDAZOLE AS AN ADJUNCT TO SCALING AND ROOT PLANING ON GLYCEMIC CONTROL IN TYPE II DIABETIC PATIENTS WITH CHRONIC PERIODONTITIS - K, Dhivya; K, Yogarajan; T S, Shanmugarajan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Periodontitis, a chronic inflammatory disease characterized by destruction of the periodontal ligament and alveolar bone is the sixth complication of diabetes mellitus. Periodontal treatment that reduces gingival inflammation aids in the control of hyperglycemia. Therefore, the present study was designed to determine the effect of treating chronic periodontitis with oral antibiotics azithromycin and metronidazole on the level of serum glycated hemoglobin in type-II diabetic patients. Methods: This prospective observational study was carried out in the dental department of a tertiary care hospital for 9 months. Clinical and biochemistry reports of 90 patients were collected in designed case report forms. All statistical analyses were performed using IBM Statistical Package for Social Sciences 17 and Graph Pad Prism 7.0. Results: Significant reduction in all the clinical and dental parameters was comparatively higher in patients who received azithromycin than in patients who received metronidazole and scaling and root planning alone. Conclusion: Periodontal therapy with oral azithromycin can be employed as a supportive strategy for the management of diabetes mellitus. Henceforth, prevention and control of periodontal disease along with antibiotics must be considered an integral part of glycemic control. However, due to the lesser sample size in this study, further investigations are required to confirm the effect of periodontal therapy on systemic diseases. Keywords: Periodontitis, Azithromycin, Metronidazole, Glycemic control, Diabetes mellitus.